Office-based Exercise Therapy as a Non-pharmacological Treatment for Discogenic Low Back Pain among Army Staff - Reza ALIZADEH; Ardalan SHARIAT; Noureddin NAKHOSTIN ANSARI; Ramin KORDI; Joshua A. CLELAND; Azadeh HAKAKZADEH; Mehdi KARGARFARD (Tehran University of Medical Sciences, 2018)
Office-based Exercise Therapy as a Non-pharmacological Treatment for Discogenic Low Back Pain among Army Staff